Picture Fuzzy MCDM Approach for Risk Assessment of Railway Infrastructure - Simić, Vladimir; Soušek, Radovan; Jovčić, Stefan (My University, 2020)
To increase the level of safety and prevent significant accidents, it is essential to prioritize risk factors and assess railway infrastructure. The key question is how to identify unsafe railway infrastructure so authorities can undertake safety improvement projects on time. The paper aims to introduce a picture fuzzy group multi-criteria decision-making approach for risk assessment of railway infrastructure. Firstly, picture fuzzy sets are employed for representing and handling risk-related information. Secondly, a picture fuzzy hybrid method based on the direct rating, and Tsallis–Havrda–Charvát entropy is provided to prioritize risk factors. Thirdly, a picture fuzzy measurement of alternatives and ranking according to compromise solution method is developed to rank railway infrastructures. Lastly, the formulated approach is implemented in the Czech Republic context. Two sensitivity analyses verified the high robustness of the formulated approach. The comparative analysis with five state-of-the-art picture fuzzy approaches approved its high reliability. Compared to the state-of-the-art picture fuzzy approaches, the provided three-parametric approach has superior flexibility.
Fuzzy přístup MCDM pro hodnocení rizik železniční infrastruktury
Keywords: risk; railway infrastructure; multi-criteria decision-making; picture fuzzy set; MARCOS; uncertainty; riziko; železniční infrastruktura; multikriteriální rozhodování; obrazová fuzzy sada; MARCOS; nejistota